Antiplasmodial Activity and Some Active Compounds from Stachytarpheta cayennensis Vahl. (Verbenaceae) Leaf Fractions - Ifeoma Chinwude, Ezenyi; Peter Achunike, Akah; Charles Ogbonnaya, Okoli (Anti-Infective Agents, 2016)
Background: New antimalarial drugs are required to fight resistant parasites and plantderived natural products are a robust source for identifying active lead compounds. Stachytarpheta cayennensis (Verbenaceae) is traditionally used in west and central Africa as malaria remedy. Objective: This study was undertaken to evaluate antiplasmodial activity of S. cayennensis leaf fractions and to isolate and identify some active constituents. Method: A dried, powdered batch of S. cayennensis leaf was extracted with hexane, dichloromethane and methanol. The methanol extract was partitioned with ethyl acetate and water. Solvent portions and ethyl acetate column fractions were investigated in early infection in mice, against chloroquine-sensitive (HB3) and chloroquine-resistant (FCM29) P. falciparum. Compounds I, II and III isolated from active fractions were identified based on their spectroscopic data and further evaluated for antioxidant and heme biomineralization inhibitory activity. Results: Column fractions 6-7, 10-11 significantly (P < 0.01) reduced parasitaemia in vivo and in vitro (IC50 < 50 μg/ml). At a dose of 2.5 mg/kg, compounds I - III significantly (P < 0.05) suppressed infection by 54.91 - 88.95 %. Compound III also displayed strong antioxidant effect (EC50 = 0.05 mg/ml) comparable to equivalent concentrations of ascorbic acid (EC50 = 0.03 mg/ml), whereas compound I elicited stronger inhibitory effect (67.93%) on heme biomineralization than compound III (38.67%). The compounds were identified as apigenin (I), stigmasterol glucoside (II) and verbascoside (III). Conclusion: The findings showed that S. cayennensis leaves contain antiplasmodial-active compounds which show potential for further development.
Keywords: plasmodium falciparum